Qatar - Reiche, D. (Comparative elite sport development. Systems, structures and public policy, 2025)
The main challenge for elite sport development in Qatar is the country's small population. By the end of 2022, the year Qatar made global headlines by becoming the first Arab country to host the FIFA men's World Cup, it stood at 2.94 million people. The demographic breakdowns in Qatar are quite unique - current estimates suggest that over 87 per cent of the population in Qatar are non-citizens, with Qatari nationals numbering around 380,000 (Mills 2022). The pool of athletes is very small: according to the State of Qatar's Planning and Statistics Authority, there were in 2021-2022 in total 19,390 athletes registered with national sports federations, 17,892 of them men and 1,498 of them women. There were only six sports with more than 1,000 registered athletes: football (4,842), swimming (2,510), athletics (1,954), handball (1,710), rugby (1,340), and volleyball (1,275). The only sport with female athletes as the majority was gymnastics (172 out of 238). The largest number of women were, apart from gymnastics, in rugby (420), tennis (262), and chess (172) (Planning and Statistics Authority, 27-28).